Images as ramparts against the demons of gambling - Francesca Antonacci (University of Bologna, 2017)
The article approaches playing as a complex experience, to understand its links with the phenomenon of gambling, thanks to some images, emblems of elements and forces which are investigated with instruments of a hermeneutic type.This interpretation aims to contribute to spreading a pedagogical problematization of gambling, a topic which has important repercussions on the most fragile sectors of the population and which today is almost exclusively the prerogative of psychologists, sociologists and economists. In this direction, in the contexts sensitive to pathological gambling, the possibility is proposed of starting up educational paths which, thanks to operating artistically, contribute to transforming the imagery of play, not simply by opposing it to a life of duty and work, but showing how it can represent a real alternative to the literality of the experience, to the fixity of the dynamics and relations, generating pleasure and well-being. It is possible to teach how to play not as a waste of time or source of alienation, nihilism or dependence but as an expression of vivifying and transformative tensions: competition in sport, defying chance in board games, identification in role play and exhilaration in rafting.